PENGARUH SUHU DAN WAKTU EKSTRAKSI TERHADAP KAFEIN DALAM KOPI - Irma Zarwinda; Dewi Sartika (UIN AR-RANIRY, 2018)
This study was conducted to determine the effect of temperature and time on the acquisition of caffeine content in coffee by UV-Vis Spectrophotometry method. The study was conducted in the AKAFARMA Laboratory of YHB Banda Aceh and the Chemical Laboratory of FMIPA Unsyiah. The sample in this study is Arabica coffee powder produced by Solong Ulee Kareng which was intentionally taken. The results showed that based on temperature, the lowest caffeine content was found at 50 °C immersion temperature, which was 0.0275 mg/g and the highest level was at 100 °C soaking temperature, which was 0.181 mg/g. Whereas, based on the time when the highest caffeine content is found at 1 hour immersion at 50 °C was about 0.0675 mg/g, at 1 hour immersion at 70 °C was about 0.0862 mg/g, and at 1 hour immersion at 100 °C was about 0.181 mg/g. The temperature and extraction time have influenced on caffeine levels in Arabica coffee. The longer the time and the higher the extraction temperature, the more extracted caffeine could be found.